Doses of organic compost in top dressing in the production of chives (Research, Society and Development, 2021)
Despite the great importance of vegetable production in the organic system, researches with organic fertilization in top dressing are rare. The objective of this work was to evaluate the effect of the organic compost applied in top dressing in the production of chives. The experimental design was a randomized complete block, with five doses of organic compost in top dressing (35.0, 52.5, 70.0, 87.5 and 105.0 t ha-1) and four replicates. Two harvests were made, the first at 60 days after transplantation and the second 30 days after the first. The following characteristics were evaluated: plant height, leaf number and fresh matter weight per plant. The higher the dose of organic compost, the greater the production of chives. The yield per plant in the first harvest ranged from 172 to 334 g, in the second harvest from 206 to 310 g and total production from 378 to 644 g for the lowest (35 t ha-1) and the highest (105 t ha-1) doses, respectively, results that confirm the importance of the organic fertilization in top dressing in the production of chives.